Quantifying the Dzyaloshinskii-Moriya Interaction Induced by the Bulk Magnetic Asymmetry - Zhang, Qihan; Liang, Jinghua; Bi, Kaiqi; Zhao, Le; Bai, He; Cui, Qirui; Zhou, Heng-An; Bai, Hao; Feng, Hongmei; Song, Wenjie; Chai, Guozhi; Gladii, O.; et al. (Physical review letters, 2022)
A broken interfacial inversion symmetry in ultrathin ferromagnet/heavy metal (FM/HM) bilayers is generally believed to be a prerequisite for accommodating the Dzyaloshinskii-Moriya interaction (DMI) and for stabilizing chiral spin textures. In these bilayers, the strength of the DMI decays as the thickness of the FM layer increases and vanishes around a few nanometers. In the present study, through synthesizing relatively thick films of compositions CoPt or FePt, CoCu or FeCu, FeGd and FeNi, contributions to DMI from the composition gradient-induced bulk magnetic asymmetry (BMA) and spin-orbit coupling (SOC) are systematically examined. Using Brillouin light scattering spectroscopy, both the sign and amplitude of DMI in films with controllable direction and strength of BMA, in the presence and absence of SOC, are experimentally studied. In particular, we show that a sizable amplitude of DMI (±0.15  mJ/m^{2}) can be realized in CoPt or FePt films with BMA and strong SOC, whereas negligible DMI strengths are observed in other thick films with BMA but without significant SOC. The pivotal roles of BMA and SOC are further examined based on the three-site Fert-Lévy model and first-principles calculations. It is expected that our findings may help to further understand the origin of chiral magnetism and to design novel noncollinear spin textures.